1987
DOI: 10.1093/jaoac/70.4.673
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Method for Determination of Potassium Guaiacolsulfonate

Abstract: The physicochemical properties of potassium guaiacol-4-sulfonate (I) and -S-suIfonate (II) have been investigated. Analyses of the X-ray diffraction patterns, infrared spectra, and thermogravimetric and differential scanning calorimetric curves showed that I occurs as crystals that are anhydrous or hydrated up to ⅔ mole (4.8%) and that II occurs as crystals that are anhydrous or dihydrated (13.5%). Solutions of I and II at various pH values showed almost the same UV spectra at <pH 6.0 but very different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Kawamura et al found that the powder diffraction pattern of PGS hemihydrate changed considerably after 2 h at 443 K under vacuum. 2 This was interpreted as formation of an anhydrate form; however, they did not quantify how much of the sample had converted. 2 In the present study, the formation of a structure different from the hemihydrate can be observed in Figure 9; additional Bragg peaks can be observed in the X-ray diffraction patterns from 430 K on indicating that the initial crystalline phase is changing.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Kawamura et al found that the powder diffraction pattern of PGS hemihydrate changed considerably after 2 h at 443 K under vacuum. 2 This was interpreted as formation of an anhydrate form; however, they did not quantify how much of the sample had converted. 2 In the present study, the formation of a structure different from the hemihydrate can be observed in Figure 9; additional Bragg peaks can be observed in the X-ray diffraction patterns from 430 K on indicating that the initial crystalline phase is changing.…”
Section: Resultsmentioning
confidence: 99%
“…2 This was interpreted as formation of an anhydrate form; however, they did not quantify how much of the sample had converted. 2 In the present study, the formation of a structure different from the hemihydrate can be observed in Figure 9; additional Bragg peaks can be observed in the X-ray diffraction patterns from 430 K on indicating that the initial crystalline phase is changing. The high-temperature pattern corresponds to the pattern for the anhydrate found by Kawamura et al (Figure 11).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations